Effects of heat treatment of TiO2 nanofibers on the morphological structure of PVDF nanocomposite membrane under UV irradiation. (December 2017) - Nor, N.A.M.; Jaafar, Juhana; Ismail, A.F.; Rahman, Mukhlis A.; Othman, M.H.D.; Matsuura, T.; Aziz, F.; Yusof, N.; Salleh, W.N.W.; Subramaniam, M.N.
Highlights: TiO2 nanofibers (TNF) were synthesized by electrospinning technique. The TNF were heat-treated under calcination temperatures of 400, 500 and 600 °C. PVDF/TNF nanocomposite membrane was prepared by hot pressing using TNF with and without undergone 500 °C heat treatment temperature. PVDF/TNF-0 and PVDF/TNF-500 show almost no apparent difference in the photodegradation of Bisphenol A (BPA) under UV irradiation. Abstract: Nowadays, photocatalytic oxidation has been pledged as a valuable process for air and water purification due to its capability in degrading organic pollutants. In this study, polyvinylidene fluoride (PVDF) nanocomposite membrane consisted of electrospun titanium dioxide nanofibers (PVDF/TNF) was prepared by hot pressing TNF onto PVDF flat sheet membrane. Titanium dioxide nanofibers (TNF) were successfully fabricated through electrospinning technique, in which electrospun from a precursor solution consisted of polyvinylpyrrolidone (PVP)/titanium tetraisopropoxide (TTIP), ethanol and acetic acid. They were then heat-treated under different calcination temperatures ranging from 400 to 600 °C. The morphological properties of TNF were characterized via scanning of electron microscope (SEM) and X-ray diffractometer (XRD). From the results collected, it is shown that the heat-treated TNF were consisted of anatase and rutile phases, whereas the un-treated TNF only possessed amorphous phase as analysed by XRD analysis. As a matter of fact, TNF-500 displayed satisfactory morphological structure, along with fiber diameter and crystalline structure compared to other TNF, thus TNF-500 was chosen for further testing. In addition, selected TNF have successfully deposited onto PVDF membrane as there is no visible lift-off. By introducing TNF into PVDF membrane matrix, said course of action resulted in a tremendously enhanced BPA photodegradation up to 85.88%. Even though the calcination process implemented on TNF has been reduced to about 4% in photocatalytic activity, further optimisation study on the loading of TNF-500 in PVDF membrane matrix could highlight favourable features of calcined TNF-500 for BPA degradation reaction.